Classroom practices in primary schools’ mathematics teaching supported by the Interactive Mathematics Software for Rwanda - Innocente Uwineza; Alphonse Uworwabayeho; Kenya Yokoyama (Institute of Advanced Engineering and Science, 2024)
Over recent decades, the integration of technological resources in education increased growingly. However, studies about the assessment of information and communications technology integration in primary school mathematics activities remained few. This research intended to comparatively examine the aspects of classroom practices observed during the implementation of the Interactive Mathematics (IM) Software in primary schools in Rwanda. Designed as quasi-experimental, it involved the experimental groups from Primary-2, Primary-3, Primary-4, and Primary-5 and analyzed aspects of school statuses, the school years, and the educational cycles. Data collected using Likert-scale measurements from 63 classroom observations were analyzed using Microsoft Excel and a two-sample t-test analysis was conducted to determine if the significance of mean differences. The findings revealed no significant difference between lower and upper primary based on a p-value of 0.829368908 (p-value>.05) and between the 2019 and 2020 teaching periods (considering the same teacher) based on the p-value=0.324542 (p-value>.05). However, the findings revealed that private and public schools’ mean differences were significant based on the calculated p-value equal to 0.007144 (p-value<.01). The study made various recommendations towards using IM software to promote quality mathematics education in primary schools in Rwanda and pre-service teacher training to boost the initiation process of their technology-enhanced pedagogy knowledge to teach mathematics.